The “priests” of East Cape: A religious movement on the Chukchi Peninsula during the 1920s and 1930s - Schweitzer, Peter; Golovko, Evgeniy (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2007)
AbstractRecently broadened fieldwork opportunities in Siberia have not only enabled the study of current social and cultural processes, but also facilitated a re-assessment of previous periods of rapid social change. One of those was, undoubtedly, the decade following the Russian Revolution, when Russians and other outsiders significantly increased their impact in many areas of Siberia. Fieldwork conducted during the 1990s has provided evidence of a previously unrecognised phenomenon, namely the existence of a syncretistic system of worldview and ritual practice in the Siberian Yupik village Naukan. Similar to so-called “revitalisation movements” elsewhere, it can be interpreted as a reaction to increasing Russian colonial pressure. The present paper attempts to situate the Naukan movement in its cultural and political contexts, in order to provide a post-colonial reading of early 20th century transformations.